The multi-level car park system - Ahmad, Asmayuzie (2001)
This paper is on designing of multi-level parking system by hardware and software methods. The project is intended to avoid congestion in parking area as a display "FULL" is placed at main entrance. So that drivers aware of the condition and don't have to waste their time searching for parking lot.